EMOTIONAL FORMS IN NIKI’S SONGS ALBUM NICOLE: PSYCHOLINGUISTICS ANALYSIS - Thirsa Ivanka Bahow; Theresia Maria Conny Lasut; Aryana N. Qarimah (Universitas Sam Ratulangi, 2025)
This study, entitled “Emotional Forms in Niki’s Songs Album Nicole: Psycholinguistics Analysis” aims to identify and classify the forms of emotions and to analyze the emotional meanings revealed by using Krech et al.'s (1969) theory within a psycholinguistics framework. The research focuses on seven selected songs from Niki’s album Nicole by listening to, reading, and underlining lyrics that indicate emotional expression. As a result, this research identified 179 instances of emotional data. The data were classified into 4 forms of emotions. However, the emotional pertaining to sensory stimulation pain was not identified. The dominant emotion found in this research was grief. The findings indicate that the emotional forms in Niki’s album Nicole follow systematic psycholinguistics patterns that shape meaning and contribute to understanding how emotions are constructed and conveyed in song lyrics.